2013
DOI: 10.31899/pgy11.1007
|View full text |Cite
|
Sign up to set email alerts
|

Girls on the Move: Adolescent Girls & Migration in the Developing World

Abstract: The Population Council confronts critical health and development issues-from stopping the spread of HIV to improving reproductive health and ensuring that young people lead full and productive lives. Through biomedical, social science, and public health research in 50 countries, we work with our partners to deliver solutions that lead to more effective policies, programs, and technologies that improve lives around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 81 publications
1
43
0
2
Order By: Relevance
“…Few (roughly 11 percent) migrated or had stopovers in smaller regional towns. This suggests that step migration may not be as common as is assumed in Ethiopia, which is consistent with other studies of migration (World Bank 2010; Temin et al 2013). Otherwise, the young age of our respondents may bias our results toward fewer post-migration residences, with a larger number of moves recorded in later years.…”
Section: Migration Historiessupporting
confidence: 89%
“…Few (roughly 11 percent) migrated or had stopovers in smaller regional towns. This suggests that step migration may not be as common as is assumed in Ethiopia, which is consistent with other studies of migration (World Bank 2010; Temin et al 2013). Otherwise, the young age of our respondents may bias our results toward fewer post-migration residences, with a larger number of moves recorded in later years.…”
Section: Migration Historiessupporting
confidence: 89%
“…Additionally, Ethiopia is experiencing a surge in rural-tourban migration, with an increase in young people migrating to urban areas in search of educational and economic advancement opportunities [6]. Young migrants are often confronted by unique social challenges such as: abuse; lack of education, parental guidance and social networks; inadequate housing and access to health services; and unstable employment conditions [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Female migrants are often at a greater disadvantage than males due to lower educational levels and gender norms that allow for subjugation of females [6]. A 2006 population-based survey of 1000 adolescents aged 10 to 19 in Addis Ababa found that nearly 25% of migrant females had moved in order to avoid family-mandated early marriages [3].…”
Section: Introductionmentioning
confidence: 99%
“…A recent global study has documented high rates of mobility among young people and calling attention to the important role that migration can play in the life of adolescents with regard to livelihoods (Temin et al 2013). Increasingly, migration is linked to accessing livelihood opportunities and safe mobility is a strong correlate of appropriate timing of workforce entry.…”
Section: Discussionmentioning
confidence: 99%